Pedagogical Conditions for Ensuring the Quality of Engineering Training in Ukraine in the 19th Century - Oleksenko, Viacheslav (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2020)
This article discusses the research results of the didactic system of training engineers at the Kharkiv Practical Technological Institute (Ukraine). It establishes the historical context for the founding of the first technical institute on the Left-Bank of Ukraine, including accounting for the great need for civilian private enterprises in engineering personnel, as well as the influence of businessmen. In carrying out the institutional analysis of the basic organizational and normative documents that regulate the educational process, particular attention is paid to class schedules and curricula from the opening of the institute in 1885 to 1891. The article comprehensively outlines the components of ensuring the quality of engineering training and considers the modernization of the process of training engineers. It also identifies and substantiates information parameters of the students, including the social status of future engineers by estate and faith. This research produces a holistic understanding of student training and expulsion. The research results are based on archival materials and literature of the 19th century.